2019
DOI: 10.1159/000495472
|View full text |Cite
|
Sign up to set email alerts
|

The miR-183/96/182 Cluster Regulates Macrophage Functions in Response to <b><i>Pseudomonas aeruginosa</i></b>

Abstract: Macrophages (Mϕ) are an important component of the innate immune system; they play critical roles in the first line of defense to pathogen invasion and modulate adaptive immunity. MicroRNAs (miRNAs) are a newly recognized, important level of gene expression regulation. However, their roles in the regulation of Mϕ and the immune system are still not fully understood. In this report, we provide evidence that the conserved miR-183/96/182 cluster (miR-183/96/182) modulates Mϕ function in their production of reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 38 publications
5
49
0
Order By: Relevance
“…For instance, miR-96 in human retinal pigment epithelial cell stimulated with hydrogen peroxide (ROS inducer), was found to be strongly downregulated (Ayaz and Dinc, 2018). Conversely, overexpression of the miR-183/96/182 cluster resulted in a decreased production of nitrite and ROS by macrophage (Muraleedharan et al, 2019) and a neuroprotective role in the brain, by positively regulating glutathione (GSH) levels, a major tissue antioxidant (Kinoshita et al, 2014). Collectively, these studies support the possibility that miR-96 can be decreased in hyperoxic/ oxidative stress conditions; this does not exclude other mechanisms such as extracellular vesicles (Liu and Lu, 2015;Battaglia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-96 in human retinal pigment epithelial cell stimulated with hydrogen peroxide (ROS inducer), was found to be strongly downregulated (Ayaz and Dinc, 2018). Conversely, overexpression of the miR-183/96/182 cluster resulted in a decreased production of nitrite and ROS by macrophage (Muraleedharan et al, 2019) and a neuroprotective role in the brain, by positively regulating glutathione (GSH) levels, a major tissue antioxidant (Kinoshita et al, 2014). Collectively, these studies support the possibility that miR-96 can be decreased in hyperoxic/ oxidative stress conditions; this does not exclude other mechanisms such as extracellular vesicles (Liu and Lu, 2015;Battaglia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most prominent findings is that miRNAs modulate the ocular infection through its regulation on innate and adaptive immunity. In PA keratitis, both miR-155 [132] and the miR-183/96/182 cluster [136,137] have been shown to suppress phagocytosis and intracellular bacterial killing of PA by neutrophils and Mϕ. Knockout or knock-down of the function of miR-155 and the miR-183/96/182 cluster resulted in increased phagocytosis and bacterial killing, which contributes to the decreased severity of PA keratitis in the ko mice.…”
Section: Discussionmentioning
confidence: 99%
“…For miR-155, Yang et al showed that Rheb, which can directly interact with mTOR and increase mTOR activity [133,134], is targeted and mediates the regulation of miR-155 on bactericidal capacity of innate immune cells [135]. In contrast, for the miR-183/96/182 cluster, Nox2, one of the key enzymes required to generate superoxide and other bactericidal ROS and RNS, is targeted by miR-182 and 96, contributing to its effect on phagocytosis and bacterial killing by Mϕ and neutrophils [136,137].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations